CON LA MANO IZQUIERDA… ¡Y TAMBIÉN CON LA DERECHA! ¿Es posible que un contratante solicite una indemnización por una causal distinta de aquella en la que sustentó la resolución del Contrato? - Castillo Freyre, Mario (2024)
This paper analyzes the feasibility of a contracting party requesting an indemnity for a reason other than the one on which the termination of the contract was based. For this purpose, two theories have been evaluated: incompatibility and compatibility. The first one states that it is necessary that whoever demands the termination of the contractual relationship and the recognition of an indemnity right, invokes the same cause as a basis for its claims. On the other hand, the second admits the compatibility of both claims, denying that the faithful contracting party, who has a unilateral termination right under the contract, is forced to resort to termination for non-performance in order to preserve its right to damages. Our conclusion is that only the thesis of compatibility is admissible, since this thesis is in accordance with the way in which the figures of termination and contractual liability are regulated and, also, because it is the position that is in accordance with the principles of justice and efficiency that should always guide the application of legal institutions.